(untitled) (Research, Society and Development, 2021)
The present work aims to analyze the evidence protection technique and its effectiveness in forensic practice. Approach the origins and historical evolution of the temporary protections, focusing on the evidence and its legal evolution. Aim to inquire the low usage reasons of the institute. Its presented some ways examples that law operators can use the institute to achieve more effectiveness in judicial proceedings. The study is based on deductive methodology by bibliographics and legislation. At the end of the study, it concludes that even though the institute exists for a long time, probably its disuse relates to a cultural issue, since the most part of the legal community just remembers the urgency protection and forgot about the evidence protection and its effectiveness.